The impact of economic growth on residential segregation: a Lephalale case study - Molefe, Sibusiso (My University, 2018)
South African cities were built under apartheid even though some of them only got city status post apartheid. Due to colonialism and subsequently apartheid, all South African cities have similar patterns of sprawl, separate land uses and segregation. Redressing socio-economic imbalances of the past has been on the ruling party’s agenda since the dawn of democracy and addressing these in human settlements is no exception. With Lephalale (formerly Ellisras) anticipated to be the first settlement built into a city post-apartheid due to its economic boom, this research investigated what is being done to create a post-apartheid envisaged city and the human settlements trends coming out of the boomtown. Since post-apartheid policies, advancing a new deal for South African cities and towns, inculcate high-density compact development, the compact city model was applied to the study to analyse the approaches and actions undertaken in the development of Lephalale. Through in-depth interviews and document analysis, the study investigated the efforts of the municipality and other stakeholders to implement the policies and principles that promote inclusive high-density compact development. Observations were key in determining the emerging human settlement trends in the municipality. The study found that Lephalale is not offering a model for post-apartheid city planning. The reasons identified included lack of a systematic boomtown strategy by the municipality and lack of coherent and coordinated approach by public and private sector stakeholders. Furthermore, there seems to be no lessons learned from former boomtowns particularly Johannesburg and Emalahleni. Existing policies that promote high-density compact development are not pursued with vigour resulting in the private developers implementing projects that further perpetuate apartheid characteristics. The study recommends formulation of a context-specific policy that meets current needs of the economic boom while addressing its long-term spatial vision. There is also a need to diversify the economy in order to create enough thresholds to transcend the boom period. Furthermore, a strategy to collect rates and taxes thus extracting value from the investment taking place to create capacity within the municipality is needed. Lastly, stronger partnering of the government, corporations and the housing industry is required to ensure a successful win-win outcome.
A dissertation submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree: Master of Built Environment (Housing), 2018